Selection of optimal composition of MR fluid for a brake designed using MOGA optimization coupled with magnetic FEA analysis. (September 2021) - Acharya, Subash; Saini, Tak Radhe Shyam; Sundaram, Vishal; Kumar, Hemantha
The design of Magnetorheological (MR) brake and the composition of MR fluid (MRF) used in it have a significant effect on its performance and hence an effort has been made in this study to determine the optimal dimensions of MR brake and composition of MRF suitable for the brake application. Initially, optimum parameters of MR brake were computed considering the properties of commercially available MRF 132DG fluid using multi-objective genetic algorithm (MOGA) optimization. This was performed in MATLAB software coupled with magnetostatic analyses in ANSYS APDL software. The braking torque of designed MR brake utilizing MRF 132DG fluid was experimentally determined and validated with analytical ones. Further, selection of optimal composition of MRF was done considering In-house MRF samples composed of different combinations of particle mass fractions, mean particle diameters and base oil viscosities. A design of experiments (DOE) technique was employed and braking torque corresponding to the synthesized MRF samples at different speeds and current supplied were measured along with the variation of shaft speed during braking process. Grounded on the experimental results, using MOGA optimization technique, MRF composed of smaller sized iron particles (2.91 microns) with mass fraction of 80.95% and lower viscosity base oil (50 cSt) was selected as optimal composition of MRF for use in MR brake. Maximization of field induced braking torque and minimization of off-state torque were chosen as the objective functions for both the optimal design of MR brake and selection of optimal composition of MRF. Finally, the sedimentation stability of MRFs were investigated.